Two-End-Member Mixing in the Fluids Emitted From Mud Volcano Lei-Gong-Huo, Eastern Taiwan: Evidence From Sr Isotopes - Chao, Hung-Chun; You, Chen-Feng; Lin, In-Tian; Liu, Hou-Chun; Chung, Ling-Ho; Huang, Chun-Chang; Chung, Chuan-Hsiung (Frontiers in Earth Science, 2022)
Mud volcano is one of the most important conduits for deep seated materials to migrate upward in sedimentary basins, convergent margins, and subduction zones. Understanding their temporal and spatial characteristics and variations provides us the important information on fluid sources and chemical compositions at depth. Mud volcano Lei-Gong-Huo (MV LGH) is a unique mud volcano which is located on the mélange formation lying on the andesitic volcanic arc. Fluids emitted from 46 mud pools in MV LGH in eastern Taiwan were sampled and their major, trace constitutes as well as H, O, and Sr isotopes (87Sr/86Sr and δ88Sr) were measured. Major constitutes of the fluids are Cl-, Na and Ca. Compared with seawater, LGH fluids have lower Cl-, δD, δ18O, Na/Cl, K/Cl, and Mg/Cl but higher Ca/Cl ratios, indicating water-rock interaction of igneous rock and the ancient seawater at the source region. This interpretation is further supported by Sr isotopes, which show low value of 87Sr/86Sr ratio down to 0.70708. The result of spatial distribution showing strong negative correlation between Na and Ca concentration as well as Ca and 87Sr/86Sr ratios indicates that two end-member mixing is the major chemical characteristic. The fluids interacting with igneous rock carry high Ca, high δ88Sr, low Na and low 87Sr/86Sr ratio while those interacting with sedimentary rock carry low Ca, low δ88Sr, high Na and high 87Sr/86Sr ratio. The source from the igneous region dominates the eastern and southeastern parts of the mud pools while sedimentary source dominates the western and northwestern parts. Most mud pools show mixing behavior between the two sources. Some of sedimentary-dominated mud pools reveal existence of residual ancient water as indicated by 87Sr/86Sr. The major factor to fractionate the stable Sr isotopes in LGH waters is the source lithology. In summary, fluids emitted by mud pools in LGH originate from two sources, which are water-rock interaction of igneous rock with the ancient seawater from the east and sedimentary rock from the west at depth, resulting from the complex geologic background of mélange formation.